Inclusion in the World Health Organization Model List of Essential Medicines of Non-Vitamin K Anticoagulants for Treatment of Non-Valvular Atrial Fibrillation: A Step Towards Reducing the Burden of Cardiovascular Morbidity and Mortality. Issue 1 (6th August 2020) - Zaidel, Ezequiel J.; Leng, Xinyi; Adeoye, Abiodun Moshood; Hakim, Ferdous; Karmacharya, Biraj; Katbeh, Asim; Neubeck, Lis; Partridge, Stephanie; Perel, Pablo; Huffman, Mark D.; Cesare, Mariachiara Di
Non-vitamin K antagonist oral anticoagulants (NOACs) represent a paradigm shift in the treatment of non-valvular atrial fibrillation (AF) with major practice guidelines around the world recommending NOACs over vitamin K antagonist oral anticoagulants for initial treatment of AF for stroke prevention. Here we describe the evidence collated and the process followed for the successful inclusion of NOACs into the 21st WHO Model List of Essential Medicines (EML). Individual NOACs have been reported to be non-inferior or superior to warfarin in preventing stroke and systemic embolism in eligible AF patients with a reduction in the risk of stroke and systemic embolism and a lower risk of major bleeding in patients with non-valvular AF compared with warfarin in both RCTs and real-world data. The successful inclusion of NOACs in the WHO EML is an important step forward in the global fight against cardiovascular morbidity and mortality, especially in low- and middle-income countries, where the burden of disease is high and limited access to diagnosis and treatment translates into a higher burden of morbidity, mortality, and economic costs.